Charakternye osobennosti fiziceskoj podgotovlennosti begunov na srednie distancii - Kobyakova, Yu. P.; Baishev, A. A.; Cherkashina, E. V.; Sharina, S. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article discusses the physical preparedness of athletes specializing in middle distance running. As a result of examination of the athletes and assessment of the level of development of physical qualities and abilities, uneven development of all the components of physical preparedness was found. For middle-distance runners, speed endurance, on the level of development of which the competitive result is more dependent on, corresponds to a lower average level, and for runners to a low level, however speed training corresponds to a level above average. Training tools introduced into the training process, such as running uphill; running with weights on segments 400-800 m; repeated and alternate runs on 300-600 m segments with a competitive speed of 800 m positively influenced the development of not only endurance, but also speed and strength abilities of athletes.